The constitution of the portal vein in bovines of Nelore breed - Zanco, Nilton Abreu; Reginato, Ana Luisa; Miglino, Maria Angélica; Didio, Liberato João Afonso (Brazilian Journal of Veterinary Research and Animal Science, 1994)
The constitution of the portal vein in Nelore bovines has been studied in 30 fetuses. The extrahepatic portion of the portal vein and its roots were injected with colored Neoprene latex and, then, dissected. Variations in the arrangement of the tributaries and branches of the portal vein were described. The most frequent disposition was the portal vein constituted of the esplenic, gastroduodenal and cranial mesenteric veins.